2023
DOI: 10.1007/s12325-023-02541-x
|View full text |Cite
|
Sign up to set email alerts
|

Natamycin Ocular Delivery: Challenges and Advancements in Ocular Therapeutics

Abstract: Fungal keratitis, an ocular fungal infection, is one of the leading causes of monocular blindness. Natamycin has long been considered the mainstay drug used for treating fungal keratitis and is the only US Food and Drug Administration (USFDA)-approved drug, commercially available as a topical 5% w/v suspension. Furthermore, ocular fungal infection treatment takes a few weeks to months to recover, and the available marketed antifungal suspensions are associated with poor residence time, limited bioavailability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Natamycin exhibits broad-spectrum activity and is particularly effective against Fusarium spp., a common cause of fungal keratitis, as well as Aspergillus spp. [ 14 ]. Natamycin is typically administered topically as eye drops or ointment and is generally well-tolerated with minimal systemic absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natamycin exhibits broad-spectrum activity and is particularly effective against Fusarium spp., a common cause of fungal keratitis, as well as Aspergillus spp. [ 14 ]. Natamycin is typically administered topically as eye drops or ointment and is generally well-tolerated with minimal systemic absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal susceptibility testing could provide valuable information on the susceptibility of fungal isolates to natamycin and help to guide treatment decisions, particularly in cases of refractory or recurrent fungal keratitis. However, MIC results should be interpreted in conjunction with clinical data and other factors, such as corneal penetration of the antifungal agent and patient response to therapy, to optimise treatment outcomes [ 14 ]. Additionally, natamycin MIC testing was not available over the course of this study.…”
Section: Discussionmentioning
confidence: 99%
“…NAT exhibits stronger antifungal activity, lesser side effects, and lower resistance rates compared to other antifungals, which support its treatment efficiency in FK, especially in superficial FK. 7,8 Nevertheless, previous reports demonstrated that only 7.6% of FK patients could be resolved by topical antifungals. 9 On the one hand, drug-resistant fungal infections are emerging as an important clinical problem.…”
mentioning
confidence: 99%